Ukranian verbs with multiple prefixes in the language of the inhabitants of Jarzeń - Czetyrba-Piszczako, Mirosława (Papers in Linguistics, 2020)
The article focuses on the formation of verbs with multiple prefixes that are preserved in the dialect of Jarzeń – a village in Braniewo County (Warmian-Masurian Voivodeship). The aim of the article is to identify types of morphemes creating multiple prefixes and to analyse their application. The verbs included in the research were extracted from recordings taken during a visit in the aforementioned region. Their classification, based on types and number of prefixes, has shown that among verbs with multiple prefixes, those with two prefixes are most common. Verbs with a higher number of prefixes are less common. The prefix po- (по-) is most often applied in already prefixed verbs and is followed by the prefix na- (на-). In the analysed verbs the attachment of a secondary prefix determines its semantic function, which expresses cumulativeness and plurality.